Pemberian Hak Restitusi Terhadap Anak Sebagai Korban Tindak Pidana Kekerasan Seksual - Marikas Bertha Suitela; Marlyn Jane Alputila (Jurnal Restorative Justice, 2023)
There are still many children who are victims of crime, one of which is the crime of sexual violence. Sexual violence against children can impact children's health and cause lasting trauma even until the child grows up. The form of legal protection for children who are victims of crime is by providing restitution for the child. Restitution is a compensation payment charged to the offender based on a court decision with permanent legal force. This study aims to determine how restitution is arranged for children who are victims of sexual violence and to find out the application of the right of restitution to child victims of sexual violence in the Merauke Regency. This research is a type of empirical juridical research, with bibliographical and field data collection techniques and analyzing data qualitatively. The results of the research conducted by the author show that the legal basis for carrying out requests for restitution is Law Number 35 of 2014 concerning Child Protection and Government Regulation Number 43 of 2017 concerning Implementation of Restitution for Children who are Victims of Crime. The government or law enforcers can provide socialization to the public regarding the rules regarding criminal acts of sexual violence against children. Children who have become victims of criminal acts have rights regulated in laws and regulations. And in Merauke Regency, the implementation of the right of restitution for child victims of sexual violence has not yet been fulfilled because there are still several obstacles, one of which is that in Merauke Regency itself, there is no LPSK which makes it difficult for the public prosecutor to determine the amount of the cost of restitution. The government is expected to be able to open LPSK representatives in Merauke Regency so that the provision of compensation and reimbursement can run effectively and efficiently.